Gravitational lensing by deformed Horava-Lifshitz black hole in rainbow gravity - Aniruddha Ghosh; Ujjal Debnath (Physics Letters B, 2025)
In this study, we investigate the gravitational lensing effects of deformed Horava-Lifshitz black holes, considering both strong and weak-field limit approximations and incorporating the impact of rainbow functions. Initially, we numerically compute the coefficients of the deflection angle, a¯, b¯, and ups/Rs, and plot the deflection angle αd as a function of the impact parameter u. We then proceed to calculate observable quantities, including the angular deflection θ∞, the total deflection area S, and the radius of the multiple gravitational arcs, rmga, for supermassive black holes such as M87⁎, SgrA⁎, and NGC4649. Additionally, we examine the Einstein ring, θnE, for a range of supermassive black holes. Using the Gauss-Bonnet theorem, we derive the deflection angle in the weak-field limit for deformed Horava-Lifshitz black holes while considering rainbow functions. The results are compared with those for a Schwarzschild black hole, where α=0 and g,h=1.